Self-preservation of Health and Personality among Students with Disabilities in the Inclusive Education as a Problem Statement - Osmuk, L.A. (Psihologičeskaâ nauka i obrazovanie, 2023)
The article describes the conceptualization of the health and personality self-preservation among students with disabilities, which is associated with the necessity to expand the methodological boundaries of the study and social modeling in inclusive education. There are considered features of the denoted social group self-preservation reactions, self-preservation behavior and self-preservation strategy. Starting from the assumption that self-preservation presupposes reaction to threats of different levels, a three-level model of the phenomenon is proposed: 1) physical and mental health self-preservation as reaction to internal and external threats; 2) self-preservation personality; 3) self-preservation of the social environment. The development of the model is based on the principle of contextually taking into account the uncertainty of modern society status, which involves numerous threats to human health and life. The connection between the conscious necessity for self-preservation and active behavior is emphasized. Within the inclusive university framework, it is possible to create successful self-preservation strategies, despite the stringent requirements for professional training, which are observed through comprehensive support for students with disabilities. Представлена авторская попытка концептуализации проблемы самосохранения здоровья и личности студентов с инвалидностью. Отмечается, что это связано с необходимостью расширения методологических границ изучения и социального моделирования инклюзивного образования. Рассматриваются особенности самосохранительных реакций, самосохранительного поведения и самосохранительной стратегии обозначенной социальной группы. Отталкиваясь от предположения, что самосохранение предполагает реакцию на угрозы разного уровня, предлагается трехуровневая модель феномена: 1) самосохранение физического и психического здоровья как реакция на внутренние и внешние угрозы; 2) самосохранение личности; 3) самосохранение социальной среды. Разработка модели основывается на принципе контекстуальности: учитывается состояние неопределенности современного общества, предполагающее многочисленные угрозы здоровью и жизни человека. Подчеркивается связь осознанной необходимости самосохранения с активным поведением. В рамках инклюзивного вузовского образования возможно конструирование успешных стратегий самосохранения, несмотря на жесткие требования к профессиональной подготовке, что обеспечивается через комплексное сопровождение студентов с инвалидностью.